The Antagonism of 5-HT6 Receptor Attenuates Current-Induced Spikes and Improves Long-Term Potentiation via the Regulation of M-Currents in a Pilocarpine-Induced Epilepsy Model - Zhu, Chaofeng; Lin, Rong; Liu, Changyun; Huang, Mingzhu; Lin, Feng; Zhang, Gan; Zhang, Yuying; Miao, Junjie; Lin, Wanhui; Huang, Huapin (Frontiers in Pharmacology, 2020)
Recent studies have documented that reduced M-current promotes epileptogenesis and attenuates synaptic remodeling. Neurite growth is closely related to the level of 5-HT6 receptor (5-HT6R) in the central nervous system. However, little literature is available regarding the relation between 5-HT6R and M-current and the role of 5-HT6R in M-current regulation. Herein, we found that the expression of 5-HT6R was notably increased and the expression of KNCQ2/3, the main components of M channel, was decreased in a time-dependent manner in pilocarpine-induced chronic epileptic hippocampus. Interestingly, the antagonism of 5-HT6R by SB271046 up-regulated the expression of KCNQ2, but not KCNQ3. SB271046 greatly alleviated excitatory/inhibitory imbalance, and improved the impaired LTP in the chronic epileptic hippocampus. Further mechanism exploration revealed that the above effects of SB271046 can be reversed by the M-channel inhibitor XE991, which also confirmed that SB271046 can indeed improve the abnormal M current. These data indicate that the antagonism of 5-HT6R may decrease the excitability of hippocampal pyramidal neurons in the chronic epileptic rats and improve the impaired long-term potentiation by upregulating the expression of KCNQ2 in the M-channel.